Factores de competitividad en las agencias de viajes de turismo de Manabí - Holguín Pincay, Daniela Dayana (2024)
The objective of this research was to determine the competitiveness factors that influence the performance of tourism travel agencies in the province of Manabí. For this study, three phases were established: the first was the characterization of the agencies, which consisted of identifying the range of products and services offered by the operators of Manta, Portoviejo and Puerto López, in relation to their typology and competencies; the client profile was obtained by analyzing the results of surveys and the SPSS system. The second phase was based on the evaluation of the quality of tourist services provided by the travel agencies, for which an analytical-synthetic approach and the Delphi method were used, combining techniques such as expert criteria and bibliographic review through which competitiveness factors in travel agencies were selected, the validation of standards was carried out by nine tourism marketing specialists, who selected the indicators with the highest score, considering the implementation of competitiveness factors in various areas. In the third phase, strategies related to the dimensions of the competitiveness factors were proposed, which was carried out by using the 5W2H matrix. The purpose of this research is to apply competitiveness factors to strengthen the performance and positioning of the travel agencies of Manabí in the tourism market.